Optimasi Dosis Madu Kelor Pada Ibu Menyusui Terhadap Keberhasilan Menyusui dan Pertumbuhan Bayi Usia 1-5 Bulan - A Sukara, Muhammad Akmal; Syamsuryanita, Syamsuryanita; Irmasari, Irmasari; Faisal , Farasmawati (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Introduction: Honey has long been recognized as a herbal substance with substantial health benefits, including its potential role in supporting successful breastfeeding and infant growth. One type of honey that has recently gained attention is Moringa oleifera honey (moringa honey), which is rich in essential nutrients and bioactive compounds that may contribute to improving both the quality and quantity of breast milk and potentially preventing stunting. This study was conducted in Maros Regency, an area characterized by a high prevalence of stunting and low coverage of exclusive breastfeeding. Previous studies primarily focused on the benefits of moringa honey supplementation among pregnant women at a dose of 15 ml/day for eight weeks. However, no studies have specifically examined the effects of moringa honey supplementation on breastfeeding success and infant growth, nor have they explored optimal dosing in lactating mothers. Therefore, this study aimed to determine the optimal dose of moringa honey for enhancing breastfeeding success and promoting growth among infants aged 1–5 months Methods: This study employed a Randomized Controlled Trial (RCT) design with three intervention groups receiving moringa honey at doses of 10 ml/day, 15 ml/day, and 20 ml/day, respectively. Lactating mothers with infants aged 1–5 months were randomly assigned to the intervention groups and received supplementation for four weeks. Breastfeeding success was assessed using a validated breastfeeding success questionnaire, while infant growth was evaluated through measurements of body weight and body length. Data were analyzed using appropriate statistical tests to identify the effective and optimal dose of moringa honey. Differences between intervention and control groups were analyzed using the Independent t-test and Mann–Whitney U test. Within-group pre–post differences were assessed using the Paired t-testand Wilcoxon signed-rank test. Comparisons across all intervention groups were conducted using one-way ANOVA and the Kruskal–Wallis test. Results: Overall, the findings reinforce the potential of moringa honey as a safe and beneficial herbal intervention for supporting breastfeeding success and infant growth. Comparable effects were observed across all dosage groups, indicating that a lower dose of 10 ml/day is sufficient to confer measurable benefits. This has important practical implications, as lower doses are more feasible, safer, and more affordable for community-level implementation. Given the persistently high prevalence of stunting and low rates of exclusive breastfeeding in many regions, moringa honey may serve as a complementary nutritional intervention that is readily acceptable to lactating mothers. Although no statistically significant differences were observed between dosage groups, the results demonstrate the clinical relevance of moringa honey in supporting lactation and infant growth. Conclusion: Supplementation with moringa honey at doses of 10 ml, 15 ml, and 20 ml per day for one month significantly improved breastfeeding success scores and infant growth, with no significant differences among the dosage levels. The similar magnitude of improvement across all groups suggests that the beneficial effects of moringa honey on lactation and infant growth can be achieved even at lower doses. These findings indicate that moringa honey is a safe herbal intervention with promising potential to support maternal and infant health.